2019
DOI: 10.1002/fsn3.1128
|View full text |Cite
|
Sign up to set email alerts
|

Lower methionine/cystine ratio in low‐protein diet improves animal reproductive performance by modulating methionine cycle

Abstract: Background As the extend of low‐protein diets in many countries including China, more researches of amino acid nutrition (AA) have been carried out. But the ideal AA pattern, especially the reasonable proportion of amino acids such as the desired methionine (Met): cystine (Cys) ratios are not yet clear. Objectives In this article, the experiments of low‐protein diet with varying ratios of Met:Cys (low ratio of 1:3, medium ratio of 1:1, and high ratio of 3:1) were conducted to investigate the effect on mice gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
2
12
0
2
Order By: Relevance
“…Besides, the antioxidant capacity has been indicated to be associated with meat quality traits ( 20 ). A previous study showed that a dietary lower methionine and cysteine ratio in an LP diet improved antioxidant capacity in boar ( 38 ), while the extreme LP diet might not support well the antioxidant defense and ability to combat the stress in Chrysolophus amherstiae ( 39 ). Here, we also found that the LP diets reduced plasma MDA contents and increased the GSH contents in the plasma of finishing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the antioxidant capacity has been indicated to be associated with meat quality traits ( 20 ). A previous study showed that a dietary lower methionine and cysteine ratio in an LP diet improved antioxidant capacity in boar ( 38 ), while the extreme LP diet might not support well the antioxidant defense and ability to combat the stress in Chrysolophus amherstiae ( 39 ). Here, we also found that the LP diets reduced plasma MDA contents and increased the GSH contents in the plasma of finishing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Means and standard errors of means were calculated for all parameters. Statistical differences among bulls were obtained using one-way analysis of variance with Duncan's multiple range test (SPSS 21.0) and p<0.05 was considered statistically significant [29].…”
Section: Discussionmentioning
confidence: 99%
“…The sperm suspension was collected and filtered through a nylon mesh with a 38-μm pore diameter to remove tissue fragments and then used to record and calculate sperm count and abnormality according to the methods in a previous study ( Guo et al, 2019 ). The types of abnormal sperm morphology observed in this study mainly included the folded-tail, hookless, amorphous, double-head and double-tail phenotypes according to a previous study ( Chen et al, 2019 ). In addition, a FITC annexin V apoptosis detection kit Ι (BD Pharmingen, CA, United States) was applied to quantify the survival rate and apoptosis rate of sperm.…”
Section: Methodsmentioning
confidence: 99%